The impact of match status on game rhythm in NBA basketball. - Courel, J.; McRobert, A. P.; Ortega, E.; Cárdenas, D. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Faster-paced attacks in basketball increase the likelihood of scoring. Furthermore, teams and players change their activity as a response to the match situations (Gómez et al., 2013). However, there is scarce information on game rhythm when there are varying degrees of match status (i.e. the difference in points). Therefore, this study aimed to analyse differences on ball possession duration and attack effectiveness when match status varied during the game. Methods: In total, 4207 ball possessions from 25 matches (NBA Playoffs, 2011) were analysed and classified as "moderate advantage" (4 to 10 points advantaged), "balanced" (3 points advantaged to 3 points disadvantaged) and "moderate disadvantage" (4 to 10 points disadvantaged) using the k-means cluster procedure. Binomial logistic regression analysis was performed to estimate the predictive weight of ball possession duration on attack effectiveness. Student t-test and one-way ANOVA for independent samples were used to detect mean differences in ball possession duration, attack effectiveness, and match status situations. Results: Playing shorter ball possessions was associated with higher attack effectiveness. Specifically, winners (M = 3.96s, SD = 1.38s) played shorter and more effective fast breaks compared to losers (M = 4.73s, SD = 1.61s) in "moderate advantage" situations (t(89) = 2.46, p = 0.02). Moreover, losers played longer set offence possessions in "moderate disadvantage" (M = 14.05s, SD = 5.24s) compared to "balanced" (M = 12.97s, SD = 5.75S) and "moderate advantage" (M = 12.92s, SD = 5.59s) situations (F(2) = 4.20, p = 0.02), In contrast, there was no significant differences between match status for winners (F = 0.50, p = 0.61). Discussion: Results reinforce the importance of playing faster-paced attacks to increase the likelihood of scoring in basketball (Bazanov et al., 2006; Csataljay et al., 2011, Sampaio et al., 2010). Moreover, there were significant differences in the duration of ball possession when match status altered. First, winner`s played shorter fast breaks that allowed them to keep and/or increase their scoring advantage. Second, loser`s increase in ball possession in the "moderate disadvantage" situation might be due to the winner`s defensive performance. In conclusion, increasing fast break intensity and adopting strategies to slow down opponent`s game rhythm appears to be a crucial factor used to achieve and/or increase advantages in the score and winning the game.